HETERO-STEREOTYPE DALAM FILM SERI EMILY IN PARIS SEASON 1 - Satiakemala, Silvi; Agustina, Dian (JURNAL ILMU BUDAYA, 2024)
This research aims to describe the hetero-stereotypes that appear in the film series "Emily in Paris" Season 1. The romantic comedy film series Emily in Paris Season 1 raises inaccurate cultural stereotypes about groups of French society who come from other social groups. Hetero-stereotype is a form of cultural stereotype. Hetero-stereotype refers to stereotypes that are held related to other groups. Hetero-stereotype refers to a group's perception of the traits, characteristics, or values of members of another group with a tendency to define other people as having rigid ethnic characteristics and generalize about other groups (Pastor: 2013). The method used in this research is descriptive qualitative. The findings of this research gave rise to 2 (two) forms of cultural stereotypes, namely positive and negative hetero-stereotypes.